Efektivitas Pembelajaran Berbasis Proyek (Project-Based Learning) dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Matematika Kelas VII SMP Negeri 5 Setu - Yuana Yuana (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study aims to determine the effectiveness of Project-Based Learning (PBL) in improving students' critical thinking skills in mathematics at Grade VII SMP Negeri 5 Setu. The research type used is experimental with a one-group pretest-posttest design. Data were collected through a critical thinking skills test administered at three stages: pre-cycle, cycle 1, and cycle 2. The results show a significant improvement in students' critical thinking skills, with the average test score reaching 57.5% in the pre-cycle, 72.8% in cycle 1, and 85.6% in cycle 2. Based on these results, it can be concluded that Project-Based Learning is effective in improving students' critical thinking skills in mathematics at SMP Negeri 5 Setu.